Skin Punctures in Preterm Infants in the First 2 Weeks of Life - Finn, Daragh; Butler, Daryl; Sheehan, Orla; Livingstone, Vicki; Dempsey, Eugene M. (American Journal of Perinatology, 2018)
Objective The objective of this study was to investigate frequency and trends of skin punctures in preterm infants.Study Design A prospective audit of preterm infants less than 35 weeks admitted over a 6-month period to a tertiary neonatal intensive care unit. Each skin puncture performed in the first 2 weeks of life was documented in a specifically designed audit sheet.Results Ninety-nine preterm infants were enrolled. Infants born at < 32 weeks' gestation had significantly more skin punctures than infants > 32 weeks (median skin punctures 26.5 vs. 17, p-value < 0.05). The highest frequency of skin punctures occurred during the first week of life for infants > 28 weeks' gestation (medians 17.5 in 28–31 + 6 weeks' gestation, and 15 in > 32 weeks), and during the second week of life for those born at < 28 weeks (median 17.5). Infants with sepsis had more skin punctures (p-value < 0.001), but this was not significant on multivariate analysis. Median skin punctures in the second week of life were statistically higher in the sepsis group on multivariate analysis (odds ratio: 1.07, 95% confidence interval: 1.00–1.14, p = 0.041).Conclusion Frequency of skin punctures is influenced by gestational age and postnatal age. Skin punctures were not an independent risk factor for sepsis.
Keywords: neonatal intensive care; newborn; infant; preterm; procedure; sepsis